Localization and Functional Characterization of an Occipital Visual Word form Sensitive Area - Zhang, Bo; He, Sheng; Weng, Xuchu (Scientific reports, 2018)
In human occipitotemporal cortex, category-specific processing for visual objects seems to involve pairs of cortical regions, often with one located in the occipital cortex and another more anteriorly. We investigated whether such an arrangement might be the case for visual word processing. In addition to the Visual Word Form Area (VWFA) located in the occipitotemporal sulcus, we observed that another region in occipital lobe with robust responses to written words (Chinese characters). The current fMRI study investigated this area’s precise location and its functional selectivity using Chinese characters and other categories of visual images (cars, chairs and insects). In all the 13 subjects we could identify a cluster of voxels near the inferior occipital gyrus or middle occipital gyrus with stronger responses to Chinese characters than scrambled objects. We tentatively label this area as the Occipital Word Form Sensitive Area (OWA). The OWA’s response amplitudes showed similar preference to written words as the VWFA, with the VWFA showing a higher degree of word selectivity, which was confirmed by the result from spatial patterns of response. These results indicate that the OWA, together with the VWFA, are critical parts of the network for processing and representing the category information for word.